Applicability of Epoxy Materials for Repairing Wet and Underwater Concrete. Issue 1 (November 2020) - Lu, Zhihua
Abstract: Concrete structures in wet or underwater environment are damaged by erosion of water medium and other external factors for a long time. The working environment is bad, and they need to be repaired in time after diseases occur. Otherwise, it will have a serious impact on the safe use and durability of the whole structure. Because there is a large amount of water in the construction environment, the repair and reinforcement of such structures often need wet or underwater construction. Based on the above background, the purpose of this study is to study the applicability of epoxy materials for wet and underwater concrete repair. In this study, the influence of steel sheet, substrate and surface treatment on the underwater bonding ability was discussed. The EM underwater performance of different curing agent and curing agent compounding was studied. The basic principle of curing agent compounding was put forward, and the comprehensive performance of EM optimized formula was tested. The results show that the underwater properties of different curing agents are very different, but it is difficult for a single curing agent to meet the comprehensive performance requirements; the use of different kinds of curing agent compounding technology is an effective means to improve its underwater properties, but the effect of different compounding methods is significantly different, when using the modified alicyclic amine and phenolic amine compounding system, After optimization, the water pull-down shear strength of epoxy solution is 20.1mpa, air pull-shear strength is 22.7mpa, air tensile strength is 41.6mpa, air compressive strength is 100.9mpa, elastic modulus is 2.53gpa, the underwater positive pull bonding strength of epoxy mortar is 4.31mpa and the failure mode is cohesive failure of base mortar block. The underwater long-term bonding performance of epoxy mortar is excellent, After immersion for one year, the strength of the specimens has not decreased significantly, which can fully meet the actual engineering needs.